The Persian Prince the rise and resurrection of an imperial archetype - Dabashi, Hamid 1951- (Stanford University Press, 2023)
"With its title borrowed from Machiavelli, The Persian Prince goes far beyond Machiavelli's wildest imagination as to how to rule the world. Hamid Dabashi articulates a bold new idea of the Persian Prince--a metaphor of political authority, a figurative ideal deeply rooted in the collective memories of multiple nations, and a literary construct that connected Muslim empires across time and space and continues to inform political debate today. Drawing on works from classical antiquity and the vast Persianate worlds from India to the Mediterranean, as well as the Hebrew Bible and European medieval mirrors for princes, Dabashi engages a diverse body of political thought to reveal the construction of the Persian Prince as a potent archetype. He traces this archetype through its varied historic gestations and finds it resurfacing in postcolonial political thought as a rebel, a prophet, a poet, and a nomad. Bringing poetics and politics together, Dabashi shows how this archetypal figure has long defined political authority throughout the wider Iranian and Islamic worlds. With meticulous attention to literary and poetic texts, moral and philosophical treatises, allegorical and anecdotal stories, sacred and secular evidence, visual and performing arts, histories of global empires and colonial conquests, this sweeping work offers a deeply learned, richly erudite, and transformative piece of critical thinking. As Dabashi shows, the Persian Prince remains the stuff of current debate across the Muslim and Persianate worlds, in contestations over the public domain and the collective will to power, and above all in the prospects of democratic institutions"--
Keywords: Archetypus; Prinz; Iran; Authority / Political aspects; Archetype (Psychology); Imperialism / Philosophy; Political science / Philosophy; Islamic countries / Politics and government